Use of Rituximab After Orbital Decompression Surgery in Two Grave’s Ophthalmopathy Patients Progressing to Optic Neuropathy - Zhang, Benping; Li, Yaling; Xu, Weijie; Peng, Bei; Yuan, Gang (Frontiers in Endocrinology, 2020)
Background: While orbital decompression can alleviate optic nerve compression and prevent further vision loss in dysthyroid optic neuropathy (DON), it cannot relieve inflammatory symptoms. Very high doses of intravenous glucocorticoids (GCs) are the first-line therapy for DON; however, the effective rate is only 40% and might be much lower in patients who fail high-dose GC pulse therapy and progressed to DON. The results of two case series studies indicated that rituximab treatment had a much better curative effect compared to very high doses of intravenous GCs but some patients required urgent orbital decompression after rituximab injection because rituximab might lead to the release of cytokines, aggravated intraorbital edema, and further vision loss. Methods: We retrospectively studied the therapeutic process of two Grave’s ophthalmopathy (GO) patients complicated with DON who failed high-dose GC pulse therapy and underwent orbital decompression. Both patients received single-dose (500 mg) rituximab treatment. Results: During more than 2 years of follow-up, rituximab treatment exhibited significant improvement in inflammatory symptoms, as manifested by a substantial decrease in Clinical Activity Score (CAS); meanwhile, the vision of both patients improved significantly and their diplopia was relieved. Conclusions: The results of this study were consistent with those of two previous case series studies indicating the significant and lasting effect of rituximab treatment on DON, especially for patients with GC resistance or recurrence after GC therapy. Orbital decompression before rituximab treatment might reduce the incidence of rapid vision loss and urgent orbital decompression surgery caused by aggravated orbital edema after rituximab injection; however, the necessity for preventive decompression surgery requires further study.